From the First Mile to Outer Space: Tamaani Satellite Internet in Northern Quebec - McMahon, Rob; Mangiok, Thomassie (University of Waterloo Library, 2013)
Across Canada, discrepancies of access to broadband exist between urban centres and rural and remote Aboriginal communities. Government, public and private sector organizations are partnering to address these digital divides. Some employ a ‘First Mile’ approach that foregrounds how community-based institutions are driving development. This article provides a First Mile case study from the Inuit territory of Nunavik. We describe the cultural, social and political contexts the people of Nunavik and their government navigated to establish broadband in the region’s 14 northern villages. The Kativik Regional Government is building and administering infrastructure that delivers public services and encourages economic development, balancing centralized efficiencies with the needs of residents in villages like Ivujivik.